2018
DOI: 10.3389/fmats.2018.00044
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Behavior of Nanophases in Polyvinyl Alcohol (PVA)/Bamboo Charcoal (BC) Nanocomposite Films

Abstract: Polyvinyl alcohol (PVA) nanocomposite films reinforced with bamboo charcoal (BC) nanoparticles were successfully fabricated via solution casting and their nanomechanical properties in terms of material phases were determined by a peak force quantitative nanomechanical tapping mode (PFQNM). Our experimental results revealed that the elastic modulus of PVA semicrystalline phase in stack-bundle form was 24 ± 4.2 GPa with the semicrystalline phase width being 20-76 nm, as opposed to 11.4 ± 3.1 GPa and 18-65 nm for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Furthermore, PVA nanocomposites were produced by adding Bamboo Charcoal (BC) nanoparticles via solution casting. Authors found an increase of lamellar size of PVA by the incorporation of BC, which in turns allowed for significant improvement in tensile strength and elastic modulus (Mohanad and Dong, 2018). In details, the incorporation of BC nanoparticles enhanced the elastic moduli of both crystalline and amorphous phases of PVA by ∼51 and ∼100%, respectively (Mohanad and Dong, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, PVA nanocomposites were produced by adding Bamboo Charcoal (BC) nanoparticles via solution casting. Authors found an increase of lamellar size of PVA by the incorporation of BC, which in turns allowed for significant improvement in tensile strength and elastic modulus (Mohanad and Dong, 2018). In details, the incorporation of BC nanoparticles enhanced the elastic moduli of both crystalline and amorphous phases of PVA by ∼51 and ∼100%, respectively (Mohanad and Dong, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…The AFM phase images of the TiO 2 /CTA nanocomposite series showed three different phases. The brightest one corresponds to the hardest sol–gel synthesized TiO 2 nanoparticles, whereas the darkest areas are related to the softest CTA matrix in which the amorphous and crystalline phases (see Figure S3) can be distinguished, as supported by the DSC results. As long as the sol–gel content increased, the formation of homogeneously dispersed aggregates of sol–gel synthesized TiO 2 nanoparticles was higher.…”
Section: Resultsmentioning
confidence: 99%